Improving the Quality of Teaching Physics Laboratory Lessons Through Modern Software Tools - Khabib Shukurullayevich Abdullayev (Academia One Publishing, 2023)
This article provides information on improving the quality of teaching physics laboratory classes using modern software tools. The main focus is on factors necessary for students to have a broader outlook and deep knowledge.
Keywords: Software; physical experiments; hardware